Fenomena Pengasuhan Model Tiger Mom dan Elephant Mom Dampaknya Terhadap Kemandirian Belajar Anak Usia 6-12 Tahun - Suprihatin, Eny (EDULEAD: Journal of Christian Education and Leadership, 2025)
In general, there are three parenting styles for children: authoritarian, democratic, and permissive parenting. The study entitled The Phenomenon of Tiger Mom and Elephant Mom Parenting Models, Its Impact on Learning Independence of Children Aged 6-12 Years, Integrated Research on Parenting Courses for Children Aged 0-18 Years Against 28 children at the Weekly Service Place for Semester V Students of STAK Terpadu PESAT Salatiga 2024. Wanting to reveal the impact of parenting as expressed by Amy Chua, namely the combination of authoritarian and classic authoritative parenting styles, called Tiger Parenting and Elephant Parenting which is similar to the style permissive or indulgent parenting towards learning independence. The study used a qualitative Phenomenology method. Final result: there are differences in parenting patterns for each child studied. There are anomalies due to parenting between theory and field facts. There are children with Tiger Mom parenting models who are less independent in learning. Only two children according to theory, are independent in learning. In relation to Elephant Mom parenting, the facts obtained are: many children fall into the category of quite independent, independent, very independent, others according to the theory are in the category of less to not independent. Conclusion of the study: there are four good impacts of parenting patterns related to learning independence. First, increased self-confidence in using learning media. Second, children show a positive response during the learning process. Third, children know how to manage and adhere to the study time that has been set and agreed upon. Fourth, children can be responsible and able to solve problems experienced. Tiger Mom parenting can produce children who are less or even not independent with various influencing factors. One of them is the child's personal factor. Likewise, Elephant Mom parenting can produce children who are very independent in learning. Also because of personal factors and the child's social environment.